PENGARUH KONTEN MEDIA SOSIAL DAN PERSEPSI HARGA TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA UNESA - Ishomi, Muhammad Dzaki; Sulistyowati, Raya (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
The reason of this think about was to decide the impact of the social media content and price perceptions on the consumptive behavior of Surabaya State University students. The sample consisted of 376 respondents who are users of the social media application, know how to buy at the social media and have made purchases at the social media. The sampling technique is using purposive sampling technique. The data collection technique uses an online questionnaire in the form of a google form, data analysis uses the SmartPLS 3.0 platform. The results of this study prove that Media sosial content influence consumptive behavior and price perceptions affect consumptive behavior.